PENGARUH STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Piranda Asaubi; Asakir Asakir (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to analyze the effect of capital structure on company performance. Capital structure is measured by Long-term debt to total asset (LTDA) and Short-term debt to total asset (STDA), while company performance is measured by Return On Asset (ROA), Return on Equity (ROE), and Tobin's Q. The purposive sampling technique is use to analize the Data of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. It was found that capital structure has a negative significant effect on company performance as measured by ROA and ROE, and capital structure has a positive significant effect on Tobin's Q. Capital structure that measured by Longterm debt to total assets (LTDA) and Short-term debt to total assets (STDA) also has an inverse non-linear U-shaped relationship to company performance as measured by ROE and Tobin's Q.